2020
DOI: 10.1021/acs.inorgchem.0c01115
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Analogues of [Ni(bpy)2]: Synthesis and Application in Carbon–Halogen Bond Activation

Abstract: The neutral, homoleptic pyridylphosphininenickel(0) complex 6-Ph 2 -PC 5 H 2 ) 2 ] (1) has been obtained by reaction of the formal Ni(0) source [(IPr)Ni(H 2 CCHSiMe 3 ) 2 ] with 2 equiv of 2-(2′-pyridyl)-4,6-diphenylphosphinine (L). Compound 1 can be oxidized both electrochemically and through the use of ferrocenium salts, to afford the corresponding Ni(I) complexes [1]BF 4 , [1(THF)]PF 6 , and [1 2 ](BAr F 4 ) 2 . The structures of these salts reveal an interesting dependence on the nature of the anion. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…An intriguing coordination mode involves bridging of two metal centers. 4 Although Venanzi and co-workers crystallographically characterized a μ 2 -P bridging phosphinine ( A , Fig. 1a) over three decades ago, 5 profound insight into the electronic structures of such μ 2 -P bridging phosphinines remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing coordination mode involves bridging of two metal centers. 4 Although Venanzi and co-workers crystallographically characterized a μ 2 -P bridging phosphinine ( A , Fig. 1a) over three decades ago, 5 profound insight into the electronic structures of such μ 2 -P bridging phosphinines remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Phosphinine can exhibit all three bridging modes illustrated in Fig. 1c; 27 Type I with a lone pair on the phosphorus atom, [28][29][30][31][32][33][34] Type II with a phosphide-like resonance structure 28,[35][36][37] or 8e donor character where both the lone pair on the P atom and p-electrons of the phosphinine ring are donated, [38][39][40] and Type III utilizing the lone pair and the low-lying p* orbital. 40,41 Mathey, Le Floch, and coworkers reported that a dinuclear ruthenium complex with bisphosphinine ligands showed Type III bridging mode (Fig.…”
Section: Introductionmentioning
confidence: 99%